Transcription complexes as RNA chaperones. Issue 4 (8th August 2021) - Said, Nelly; Wahl, Markus C.
ABSTRACT: To exert their functions, RNAs adopt diverse structures, ranging from simple secondary to complex tertiary and quaternary folds. In vivo, RNA folding starts with RNA transcription, and a wide variety of processes are coupled to co-transcriptional RNA folding events, including the regulation of fundamental transcription dynamics, gene regulation by mechanisms like attenuation, RNA processing or ribonucleoprotein particle formation. While co-transcriptional RNA folding and associated co-transcriptional processes are by now well accepted as pervasive regulatory principles in all organisms, investigations into the role of the transcription machinery in co-transcriptional folding processes have so far largely focused on effects of the order in which RNA regions are produced and of transcription kinetics. Recent structural and structure-guided functional analyses of bacterial transcription complexes increasingly point to an additional role of RNA polymerase and associated transcription factors in supporting co-transcriptional RNA folding by fostering or preventing strategic contacts to the nascent transcripts. In general, the results support the view that transcription complexes can act as RNA chaperones, a function that has been suggested over 30 years ago. Here, we discuss transcription complexes as RNA chaperones based on recent examples from bacterial transcription.